A synergistic reinforcement of Re and W for ideal shear strengths of γ′-Ni3Al phases. (August 2019) - Chen, Yi; He, Shuang; Yi, Zhou; Peng, Ping
Abstract: Using first-principles calculations, we investigate the ideal shear strengths σ max of L12 -Ni3 Al crystals with various multiple additions of Re and W. A correlation energy function Δ E Re A + W B ( d ) is adopted to evaluate the interaction between point defects (i.e., Re A and W B ). The results indicate extra addition of Re or W does not change the site preference of Re and W at Al sites, and W in preference to Re occupies Al sites. In this preferred site, σ max of L12 -Ni3 Al crystals with single Re addition is larger than that with single W addition, but the strengthening effect of double Re addition is weak compared with multiple addition of Re and W. Strong repulsion is found to be disadvantageous for the reinforcement of γ′-Ni3 Al phases, and σ max in Re A + W B complexes decreases with increasing Δ E Re A + W B ( d ) . The analysis of electronic and geometric structures reveals Re/W-addition-induced strengthening mainly originates from stronger Re/WNi bonding than AlNi bonding, but a significant increase of σ max in γ′-Ni3 Al-ReW systems is attributed to a cooperative effect of electronic interaction and local elastic strain energy, and the local elastic strain energy is dominant. Graphical abstract: Image 1 Highlights: Interaction between Re and W does not change their site preferences in Al sublattices. W in preference to Re occupies Al sites in the case of multiple addition of Re and W. Extra addition of Re/W can increase σ max in ternary Ni3 Al-Re/W crystals. Strong repulsion between Re and W is harmful to the reinforcement of γ′-Ni3 Al phases. Local elastic strain energy plays a key role in the detrimental impact of ReW repulsion.